Long Term Outcomes after Intestinal Transplantation from a Single South-American Center, Lessons Learned. (July 2018) - Farinelli, Pablo A.; Fraile, Andres; Pattin, Francisco; Ramisch, Diego; Rumbo, Carolina; Echevarria, Constanza; Nachman, Fabio; Niveyro, Silvia; Crivelli, Adriana; Martinez, Maria Ines; Trentadue, Julio; Fernandez, Adriana; et al.
Abstract : Introduction: In many countries, intestinal failure patients (IF pts) had the only option of parenteral nutrition (PN) as available treatment until intestinal transplantation (ITx) evolves as part of a multidisciplinary team. We would like to report the long-term outcomes of a series of ITx performed in children and adults at a single center, 9 years after its creation. Material and Methods: retrospective analysis of all consecutive ITx performed between May 2006 and Oct 2017. Diagnoses, pre ITx mean time on PN, indication for ITx, time on the waiting list (WL), type of ITx, mean total ischemia time (TIT), and warm ischemia time (WIT), time for PN discontinuation, 5-year actuarial patient survival are reported. Results: 44 patients received 47 ITx. The mean time on PN for the Tx group was 1604 days*. The main indication for ITx was: lack of central venous accesses followed by PN associated liver disease, and catheter related infectious complications. The mean time on the WL was 222 days (SD: 195 days). ITx were performed in 28 children and 16 adults. Thirty-seven procedures were isolated ITx; 10 multiorgan (MTO) (4 combined, 7 multivisceral - 2 with kidney); 4 (8, 5%) were re-transplants: 3 isolated, 1 multivisceral; 8 included right colon. Sixteen pts (36%) received the abdominal rectus fascia. All procedures were performed by the same team; TIT was 7:36±2:10 hs, WIT was 39.1±10.5 min. Mean length of implanted intestine: 325 ± 59.5 cm, BC ileostomy were performed in 59.5% of the cases. 18/47 Tx required early re-operations. The overall mean follow up time is 49±45.2 months; the mean time to be off PN was 68 days (* p: 0, 001); the overall 5 year pt survival is 55.1%; 60.5% for Isolated ITx vs 35% for MTO (p=0, 01); 60.3% for ped recipient's vs 44.9% for adults (p=NS). Conclusions: After 11 years of establishing a dedicated adult and ped IF program, we proved that ITX is a valid therapeutic alternative for pediatric and adult candidates. Long term results are comparable to a large series reported from centers of develop countries or the ITR.